Psoralen Promotes Proliferation, Migration, and Invasion of Human Extravillous Trophoblast Derived HTR-8/Svneo Cells in vitro by NF-κB Pathway - Qi, Dan; Lu, Jingyuan; Fu, Ziyi; Lv, Shanshan; Hou, Lili (Frontiers in Pharmacology, 2022)
Background: Recurrent spontaneous abortion (RSA) is a kind of pathological pregnancy, and abnormal function of trophoblast cells may be related to a variety of pregnancy complications including RSA. Psoralen is an effective ingredient extracted from P. corylifolia with multiple bioactivities mainly including anti-osteoporotic, anti-tumor, anti-inflammatory and estrogen-like effects. However, the exact role of psoralen on trophoblast invasiveness has not been investigated so far. Methods: The in vitro cultured HTR-8/SVneo cells were subjected to exposures at different concentrations of psoralen. Cell viability of HTR-8/SVneo cells after challenge with psoralen was determined by cell counting kit-8 (CCK-8) test. Cell migration and invasion assays (Transwell) were utilized to detect the effect of psoralen on the migration and invasion of HTR-8/SVneo cells. The expression patterns of nuclear factor κB (NF-κB)/p65, metalloproteinases (MMP)-2 and MMP-9 were then characterized by further experiments including real-time quantitative polymerase chain reaction and Western blot. Indirect immunofluorescence was applied to track the NF-κB p65 translocation. Results: In certain concentrations, cell viability was promoted by psoralen with the increase of the concentration and treatment duration. Psoralen can effectively enhance the invasive ability and expression of MMP-2 and MMP-9 of HTR-8/SVneo cells in a dose-dependent manner (P<0.05). Additionally, we observed accelerated nuclear accumulation and enhanced nuclear translocation of p65 in the presence of psoralen. Furthermore, invasiveness enhancement of psoralen on HTR-8/SVneo cells was partly eliminated by a NF-κB pathway inhibitor. Conclusion: Psoralen may promote the proliferation, migration and invasion ability of HTR-8/SVneo human trophoblast through strengthening the NF-κB pathway.